A Novel Technique For Enterocutaneous Fistula Closure- Local Transposition Flap - Kumar, Sudhir; Jain, Aakansh (Journal of Society of Surgeons of Nepal, 2023)
Enterocutaneous fistulae are one of the most dreaded complications of abdominal surgeries which may be due to the result of multiple causes like anastomotic failure, poor blood supply, or iatrogenic bowel injuries. These fistulae are classified based on their output. Most Low output fistulae usually close spontaneously but few remain patent and may require surgical intervention. We are presenting two of our cases where we have used the local transposition flap to cover the enterocutaneous fistulae successfully. It can serve as a good armour in the armamentarium of plastic surgeon.